Survival after rectal cancer: differences between hospital catchment areas. A nationwide study in Sweden. (1st July 1999) - Blomqvist, P; Ekbom, A; Nyrén, O; Krusemo, U B; Bergström, R; Adami, H-O
Abstract : BACKGROUND: The quality of rectal cancer surgery at small units has been debated. No national studies of this issue have been undertaken and most studies have been based on insufficient data to clarify the controversy. It has been claimed that observed differences in outcomes between specialised centres and smaller hospitals are confounded by differences in stage/severity. AIM: To compare survival after rectal cancer between hospital catchment areas. PATIENTS: All patients with rectal cancer notified to the Swedish Cancer Register in 1973–1992 (n = 30 811) were followed up by record linkage to the nationwide Death Register. METHODS: Relative survival—that is, ratio of observed to expected survival—was computed as a measure of excess mortality attributable to rectal cancer. Multivariate analysis was then performed to estimate the independent effects of hospital catchment area categories and age, year of diagnosis, and duration of follow up. RESULTS: One year relative survival among rectal cancer patients residing in catchment areas of large regional hospitals was 76%, compared with 72% for small local hospitals (p<0.001). A difference was already noted after 30 days and remained five years after diagnosis. Relative survival improved considerably overall, but the differences between catchment area categories persisted. These were not reduced by adjustment for age, time after diagnosis, or time period in multivariate models. CONCLUSION: The differences in outcome between catchment area categories could not be explained by differences in age, time period, or duration of follow up after diagnosis. They are unlikely to be explained by differences between catchment area populations with regard to the average stage of the disease at which symptoms lead to diagnosis. The differences may therefore be attributable to different strategies for diagnosing and managing patients with rectal cancer.